Effects of stenosis and dilatation on flow of blood mixed with suspended nanoparticles: a study using homotopy technique - Sudha, T.; Umadevi, Chatla; Dhange, Mallinath; Manna, Santanu; Misra, J.C. (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with a theoretical study on blood flow in a stenosed segment of an artery, when blood is mixed with nano-particles. Blood is treated here as a couple stress fluid. Stenosis is known to impede blood flow and to be the cause of different cardiac diseases. Since the arterial wall is weakened due to arterial stenosis, it may lead to dilatation /aneurysm.
Keywords: stenosis; dilatation; couple stress fluid; impedance; shear stress